Cytokine adsorption in patients with severe COVID-19 pneumonia requiring extracorporeal membrane oxygenation: protocol for a randomised, controlled, open-label intervention, multicentre trial. Issue 1 (17th January 2021) - Rieder, Marina; Schubach, Fabian; Schmoor, Claudia; von Spee-Mayer, Caroline; Wengenmayer, Tobias; Rilinger, Jonathan; Staudacher, Dawid; Bode, Christoph; Duerschmied, Daniel; Supady, Alexander
Abstract : Introduction: Veno-venous extracorporeal membrane oxygenation (V-V ECMO) is a last resort treatment option in patients with severe COVID-19 related acute respiratory distress syndrome (ARDS). Mortality in these critically ill patients is high. Elevated interleukin-6 (IL-6) levels in these severe courses are associated with poor outcome. Extracorporeal cytokine adsorption is an approach to lower elevated IL-6 levels. However, there is no randomised controlled data on the efficacy of cytokine adsorption and its effect on patient outcome in severe COVID-19 related ARDS requiring V-V ECMO support. Methods and analysis: We here report the protocol of a 1:1 randomised, controlled, parallel group, open-label intervention, superiority multicentre trial to evaluate the effect of extracorporeal cytokine adsorption using the CytoSorb device in severe COVID-19 related ARDS treated with V-V ECMO. We hypothesise that extracorporeal cytokine adsorption in these patients is effectively reducing IL-6 levels by 75% or more after 72 hours as compared with the baseline measurement and also reducing time to successful V-V ECMO explantation. We plan to include a total of 80 patients at nine centres in Germany. Ethics and dissemination: The protocol of this study was approved by the ethical committee of the University of Freiburg as the leading institution (EK 285/20). Additional votes will be obtained at all participating centres. Trial registration numbers: NCT04385771 and DRKS 00021248.